P184 Efficacy of patient transferring devices in reducing low back injuries to nursing personnel. (1st September 2016) - Garg, Arun; Kapellusch, Jay
Abstract : Low-back (LB) injuries, are major problems for nursing personnel. Patient transferring devices offer engineering solutions to reduce biomechanical stressors; however, there is large variation in the reported reduction in LB injuries with use of these devices. The objective of this paper was to conduct a comprehensive literature review to determine the efficacy of patient lifting and transferring devices in reducing low back injuries to nursing personnel in long-term care facilities and/or hospitals. Thirteen studies were identified that used mechanical lifts to reduce LB injuries to nursing personnel. A few studies also utilised other assistive devices such as transfer boards, walking belts, repositioning devices, shower chairs and shower gurneys. Pre- and post-intervention LB injury outcomes were compared. Nine of the 13 studies were conducted in a single nursing facility and/or for a short term (often ≤ 1 year). Only one study utilised a control group (quasi control group performing non-patient transfer tasks). Decreases in post-intervention LB injury rates as compared to pre-intervention rates ranged from 18% to 63% (mean = 35.8%). Six studies reported decreases in lost-time injury rates ranging from 30% to 64% (mean = 44.6%). Eight studies reported decreases in lost workdays ranging from 18% to 100% (mean = 68.4%). Four studies reported a decrease in restricted workdays ranging from 20% to 78% (mean = 48.1%). These intervention studies suggest that patient lifting and transferring devices are effective in reducing LB injury outcomes to nursing personnel. These devices appear more effective at reducing severity (eg, lost workdays) than incidence of LB injuries (i.e. 68.4% decrease in lost workdays versus 35.8% decrease in LB injuries). Large variations in% deceases in LB injury outcomes between studies suggests there are important factors other than patient transferring devices that play a role in reducing LB injuries to nurses.